2019
DOI: 10.2474/trol.14.285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surrounding Atmosphere on Friction Properties of Hydrophobic and Hydrophilic Ionic Liquids

Abstract: The properties of ionic liquids make them an appealing choice for use as lubricant oil. However, the effect of moisture on the friction properties of ionic liquids needs to be elucidated. Moisture affects the disappearance and growth of the lubricating layer of these liquids. To express the high friction reduction effect, the lubricating layer formed by the ionic liquids at the friction interface plays a very important role. Thus, it is necessary to evaluate the relationship between these liquid structures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Their chemical structures and purity are presented in Table 1. [BMIM] [PF6] was chosen as a reference due to its hydrophobicity, which ensures stable lubricity results in different ambient conditions [31,44]. environment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their chemical structures and purity are presented in Table 1. [BMIM] [PF6] was chosen as a reference due to its hydrophobicity, which ensures stable lubricity results in different ambient conditions [31,44]. environment.…”
Section: Methodsmentioning
confidence: 99%
“…[BMIM] [PF6] was chosen as a reference due to its hydrophobicity, which ensures stable lubricity results in different ambient conditions [31,44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been reported that water molecules can cause corrosive wear on metallic sliding materials under lubrication with fluorine-based ionic liquids [19,28]. In the case of ionic liquids that form an adsorption layer, water molecules destroy this layer at the friction interface and cause the deterioration of the lubricating properties [29][30][31]. Therefore, the practical use of ionic liquids as liquid lubricants and friction manipulation systems requires that the effects of moisture in the friction atmosphere on their lubricating properties must be clarified.…”
Section: Introductionmentioning
confidence: 99%